Applying Remotely the Challenge Based Learning Methodology in Undergraduate and Postgraduate Disciplines - Costa, Andrew Diniz da; Lucena, Carlos José Pereira de; Carvalho, Gustavo Robichez de (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2023: Anais do III Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2023.228163, 2023)
Currently, remote learning has been increasingly adopted by different institutions, with the COVID-19 pandemic being one of the reasons to accelerate the use of this approach. Using different tools, different ways have been experimented for offering good experiences from remote classes, providing overall student support infrastructure, applying learning/teaching methodology and so forth. Challenge Based Learning (CBL) is a modern and active learning approach that has been used by different institutions around the world. It provides an efficient and effective framework for learning while solving real-world challenges. Even though it is in use in a number of different places, there is a dearth of reports offering remote CBL usage experiences. In order to contribute to this gap, this paper presents how the CBL was applied in two computing disciplines: one undergraduate and one postgraduate. From these experiences, a discussion ensued that led to the identification of important learned lessons, contributing to future remote classes applying CBL, which are shared.